Pelatihan Aplikasi Pengolah Data untuk Menunjang Percepatan Publikasi Terindeks Scopus dan Web of Science (WoS) - Susanti, Evi; Farida, Nani; Artasasta, Muhammad Ade; Suharti, Suharti; Wijayanti, Chandra; Yuliana, Shinta (LPkM Universitas Bakrie, 2025)
Scientific publications are one of the requirements for student graduation. The importance of scientific publications for students is that they can be used as a portfolio to apply for a job or get a scholarship. However, in publishing an article that is